(3geY GdghGeY aj TQM LeY GdLhGeYs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s ((3GdbGgQI HLhGQ GdLGeY GdCRgQ s)
(3ChdgG (B:s
(3GdcJGH GdKGdK(B: (3aj GdeLQhQGJ, heG Med YdjgG ef GdeLRheGJ heG jSJJHYgG ef PcQ COhGJ GdTQW ZjQ GdLGReI s
(3BNQgG (B:s
(3gcPG HkCd GdeDda QMeg Gddg s
(3fSNI QGHYI JJab aj ChdgG eY GdfSNI GdChdis
(3haj BNQgG HGNJdGa jSjQ LOkG aj HYV GdCdaGXs
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs